Konsep diri pasien penderita kanker payudara di Kota Pekanbaru - Samosir, Elda; Wirman, Welly; Rumyeni, Rumyeni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Breast cancer is one of the leading causes of death in Indonesia, including in Pekanbaru, with the number of cases continuing to increase. This study aims to analyze the self-concept of breast cancer patients, both internally and externally. Using a qualitative descriptive method with a naturalistic approach, this study involved five informants, namely patients and their treating doctors. The results showed that patients' self-concepts were influenced by three main factors: past life, environmental influences, and current conditions. Internally, patients face dynamics in accepting physical, emotional, and social changes due to cancer, while externally, family and social support play an important role in the adaptation process. This study suggests the importance of environmental support in improving the quality of life of breast cancer patients.